Profil penderita rinosinusitis kronik yang menjalani bedah sinus endoskopik fungsional di Rumah Sakit H. Adam Malik Medan 2008-2011 - Emilda Dewi; Mangain Hasibuan; Aliandri dr (Fakultas Kedokteran USU, 2012)
Background : Prevalens of chronic rhinosinusitis in Indonesia is high and many research explain about chronic rhinosinusitis that had performed functional endoscopic sinus surgery. This study is aimed to know profile of patient with chronic rinosinucitis that had performed functional endoscopic sinus surgery.Purpose : To know the profile of patient with chronic rhinosinusitis in Adam Malik General Hospital since 2008-2011. Methods : This research is a descriptive with case series design. The research use secondary data obtained from medical records of patients in Adam Malik General Hospital since 2008 untill 2011.Result : Out of 111 patients, the most common gender are men (52.3%), the most prevalent in age group 15-24 years, the most common symptom is nasal obstruction (98.7%), the most common symptom period is under one year (43.2%); the most common nasoendoscopy is oedema/mucosa obstructive in middle meatus (88.3%) and maxilla sinus is the most common sinus that attached infection (95.5%).Conclusion : Profile of patient with chronic rhinosinusitis in Adam Malik General Hospital, the most common gender are men with the most prevalent in age group 15-24 years, and the most common symptom is nasal obstruction. Keywords : chronic rhinosinusitis; functional endoscopic sinus; rhinosinusiti